What can we still learn from the Rawls-Habermas debate? A paradigm of political philosophy for liberal democracies - Nunzio Alì (Voluntas)
This article argues about John Rawls' paradigm shift in contemporary political philosophy.  In the article, this paradigm is defined as democratic insofar it claims, among other things, to leave enough room for democratic deliberations and citizens’ political autonomy. On this specific issue, Rawls and Habermas dialogue is still particularly fruitful. Both authors believe that contemporary political philosophy must be modest in some relevant theoretical and methodological aspects but they disagree on which of these aspects should be more or less modest. This article argues that when we look for the legitimate boundaries of the contemporary political philosophy, Rawls and Habermas projects should be seen as closely complementary to one another. On the one hand, the article partially agrees with Habermas’ objections to Rawls that political philosophy should not be too modest in providing orientations for the normative grounds of the political justification. On the other hand, against Habermas, the article remains on Rawls's side on the idea that political philosophy cannot be agnostic regarding the substantive and distributive issues of social justice.